Processing of Fibre and Its Application as Liquid Organic fertilizer in Oil Palm (Elaeis guineensis Jacq.) Seedling for Sustainable Agriculture - Sylvia Madusari (Faculty of Engineering Universitas Muhammadiyah Jakarta, 2019)
Liquid organic fertilizer has been developed to reduce the dependence of cultivated plants on inorganic fertilizers. based Oil palm fruit fiber, as a by-product of processing palm oil mills, potentially used as organic fertilizers. The purpose of this study was to obtain liquid organic fertilizer from fermented oil palm fruit fiber and analyze the effect of the fertilizer on the growth of oil palm seedlings. Two stages of the research were conducted. The first stage was processing the fibre into liquid organic fertilizer by chopping the oil palm fruit fiber and adding local microorganisms as activators. The fermentation process was carried out for 7 days. The second stage was applying fermented organic fertilizer (POC) to the oil palm growing media. The Completely Randomized Design Method was applied with 5 treatments, namely: P0 (subsoil with no fertilizer), P1 (soil + NPK), P2 (soil + 20 ml POC), P3 (subsoil + 40 ml POC), P4 (subsoil + 60 ml POC). The POC was applied once every week for 16 weeks. The results showed that liquid organic fertilizer had a significant effect on the height of palm seedlings at 4 MAP at 20 ml per seed. The oil palm seed growth tend to increase in several parameters observing in plant diameter, plant biomass and leaves greeness. Liquid organic fertilizer obtained from oil palm fruit fiber can be applied as alternative fertilizer in the prenursery. Further research related to the optimization of process producing liquid organic fertilizer and its application to other cultivated plants is highly recommended.